2023
DOI: 10.1017/langcog.2023.17
|View full text |Cite
|
Sign up to set email alerts
|

A usage-based approach to metaphor identification and analysis in child speech

Abstract: This paper presents a usage-based method for investigating metaphor acquisition in the speech of children aged two and above. The method draws on the strengths of the established tools for metaphor identification such as Metaphor Identification Procedure (MIP), and Metaphor Identification Procedure VU University Amsterdam (MIP-VU), and adapts them for coding and analysing metaphors in the corpora of naturalistic interactions between children and their primary caregivers, such as those stored online in the CHIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…A notable exception is that of Gottfried (1997) who showed that monolingual children as young as three can produce both conventional and novel perceptual metaphors when the stimuli prime the recognition of metaphoric similarity and the word production. This is also confirmed by naturalistic research: data from a two-year-old child, recorded on a dense sampling schedule between her second and third birthday, reveal high numbers of conventional primary metaphors already at the age of two, but only a few instances of conventional perceptual metaphors (Gaskins et al, 2023). Overall, these studies point towards two main conclusions: children aged three and above should respond well to metaphor elicitation tasks, and they should perform better on primary than perceptual metaphors.…”
Section: Metaphor Acquisition In Monolingual Childrensupporting
confidence: 60%
See 3 more Smart Citations
“…A notable exception is that of Gottfried (1997) who showed that monolingual children as young as three can produce both conventional and novel perceptual metaphors when the stimuli prime the recognition of metaphoric similarity and the word production. This is also confirmed by naturalistic research: data from a two-year-old child, recorded on a dense sampling schedule between her second and third birthday, reveal high numbers of conventional primary metaphors already at the age of two, but only a few instances of conventional perceptual metaphors (Gaskins et al, 2023). Overall, these studies point towards two main conclusions: children aged three and above should respond well to metaphor elicitation tasks, and they should perform better on primary than perceptual metaphors.…”
Section: Metaphor Acquisition In Monolingual Childrensupporting
confidence: 60%
“…Studies conducted in the context of SMT see perceptual metaphor use as developing gradually alongside growing verbal skills, verbal analogy, and alternative naming (e.g., Van Herwegen et al, 2013 ; DiPaola et al, 2019 ; Pouscoulous and Tomasello, 2019 ); those conducted in the context of CMT see primary metaphors as triggered by the underlying mappings of the conceptual system which enable sudden growth in primary metaphor use (e.g., Özçalişkan, 2005 ). While our previous work has shown that primary and perceptual metaphors do differ in terms of comprehension ( Almohammadi et al, n.d. ) and spontaneous production ( Gaskins et al, 2023 ), the elicitation task used in this experimental study puts them on a par with each other. This may be due to the fact that both metaphor types were embedded in stories of equal length and highly controlled (i.e., equally salient) story contexts, which posed (unusually) equal demands on the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two studies, however, only focus on a small subset of primary metaphors. Child metaphor production data identified in naturalistic interactions with her primary caregivers between the ages of two and three reveal that the child had a broad inventory of conventional primary metaphors in active use: primary metaphors accounted for 80% of all her metaphoric expressions, with perceptual metaphors used very rarely (3%) (Gaskins et al, 2023). This gives us reasons to believe that if a broader range of primary metaphors is included in this study, our project can capture an earlier onset of their acquisition.…”
Section: Metaphor Comprehension In Childrenmentioning
confidence: 97%